An Analysis of Gender Stereotype in Television Commercial Advertisements in Indonesia - Usrul Khotimah, Siti; Umi Handayani, Maulisidiya; Kusumaningrum, Endah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The media is one of the influential sources in shaping gender stereotypes among Indonesian people. The advertisements displayed in various television broadcasts tend to show a classification between masculine which is identical with men and feminine which is associated with women. The aims of this study are (1) to describe the gender stereotypes found in television advertisements in Indonesia; (2) Explaining the effect of gender stereotypes on advertising on product marketing. This research method uses a qualitative descriptive approach with the advertising object “Extra Joss, and Molto,